Electroclinical spectrum of childhood epilepsy secondary to neonatal hypoglycemic brain injury in a low resource setting: A 10-year experience. (July 2020) - Kapoor, Dipti; Sidharth,; Sharma, Suvasini; Patra, Bijoy; Mukherjee, Sharmila B; Pemde, Harish K
Highlights: Neonatal hypoglycemia is an important cause of epilepsy in low resource settings. 70% of neonatal hypoglycemia related epilepsy is drug resistant. West syndrome is the commonest epilepsy syndrome in this setting. Abstract: Purpose: Neonatal hypoglycemic brain injury (NHBI) is being increasingly recognized as an important cause of drug resistant childhood epilepsy in low resource settings. We report the electro-clinical spectrum of children with epilepsy secondary to NHBI. Methods: This was a retrospective study of children enrolled in the Epilepsy Clinic from January 2009 to August 2019. Data of children who had developed epilepsy after documented symptomatic neonatal hypoglycemia was collected. Details of clinical profile, seizure types, neurodevelopmental co-morbidities, EEG, neuroimaging findings and seizure outcomes were noted. Results: One hundred and seventy children were enrolled. The mean age at seizure onset was 10.3 months (SD 0.5 months). The seizures types were epileptic spasms (76.5%), focal with visual auras (11.2%), bilateral tonic clonic (7.1%), myoclonic (3.5%) and atonic seizures (1.8%). The EEG findings included classical hypsarrhythmia (49.4%), hypsarrhythmia variant (27.1%), focal occipital or temporo-occipital spike wave discharges (10.6%), multifocal discharges (4.7%), diffuse slow spike and wave with bursts of fast rhythms (2.4%), continuous spike waves during sleep (1.2%) and normal EEG (4.7%). MRI showed gliosis with or without encephalomalacia in the occipital lobe with or without parietal lobe in 96.5% of the patients. Co-morbidities included global developmental delay (91.2%), cerebral palsy (48.7%), vision impairment (48.2%), microcephaly (38.2%), hearing impairment (19.4%), and behavioural problems (16.5%). Drug resistant childhood epilepsy was seen in 116 (68.2%) patients. Conclusions: Our study highlights the varied electroclinical and radiological spectrum and the adverse epilepsy and neurodevelopmental outcomes associated with NHBI.